Hubungan Lima Pilar Sanitasi Total Berbasis Masyarakat (STBM) dengan Kejadian Stunting di Kecamatan Banggae Timur Kabupaten Majene Sulawesi Barat - Erlani, Erlani; Sahabuddin, Qhaerunnisa; Juherah, Juherah (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2025)
Stunting is a disease where a child's height is not in line with the child's age for a long time. Community-Based Total Sanitation is one of the main programs that can reduce cases of stunting in children. This agrees with research conducted by (Opu & Hidayat, 2021) which states that the Five Pillars of Community-Based Total Sanitation have an influence on efforts to reduce stunting. According to data from the Majene District Health Service, in 2022 there were 487 cases of stunting from 1913 toddlers examined in the district. This research aims to determine the relationship between the Five Pillars of Community-Based Total Sanitation and the incidence of Stunting in East Banggae District, Majene Regency, West Sulawesi. This type of research uses analytical observational with a cross-sectional design. The samples in this research were mothers with toddlers with a sample size of 94 samples. The sampling technique uses purposive sampling. Data was collected through interviews and filling out questionnaires, while data obtained from interviews and observations were tested using (chi-square test) with univariate and bivariate analysis via Statistical for Social Science (SPSS) software. The research results show that there is a relationship between open defecation and the incidence of stunting (p= 0.000). There is no relationship between washing hands with soap and household food and drink hygiene with the incidence of stunting (p = 1,000). There is a relationship between safeguarding household waste and the incidence of stunting (p= 0.000), and there is a correlation between safeguarding household liquid waste and the incidence of stunting in East Banggae District, Majene Regency (p= 0.003). There is a need to improve and add facilities and for the government to pay more attention to Community-Based Total Sanitation Achievements.